The Effects of Air Preheating and Fuel/Air Inlet Diameter on the Characteristics of Vortex Flame. (14th May 2015) - Khaleghi, Mostafa; Hosseini, S. E.; Wahid, M. A.; Mohammed, H. A.
Abstract : The effects of fuel/air inlet diameter as well as air preheating on the flame stability, temperature distribution, pollutant formation, and combustion characteristics of a lab-scaled asymmetric vortex flame have been investigated. A three-dimensional steady-state finite volume solver has been used to solve the governing and energy equations. The solver uses a first-order upwind scheme to discretize the governing equations in the space. The semi-implicit method for pressure linked equations has been applied to couple the pressure to the velocity terms. Several turbulence models were applied to predict the flame temperature and it was found that k - ε RNG has given the best results in accordance with the experimental results. The results reveal that the inlet air diameter can enhance the thermal properties and reduce the NO x emission while the inlet fuel diameter has less significant impact. Increasing diameters are accompanied with a pressure drop. It was found that preheating the air and fuel would significantly affect the flame temperature and NO x emission with constant mass flow rate.